An annotated type catalogue of the centipedes (Myriapoda: Chilopoda) held in the Zoological Museum Hamburg - Thofern, Detlef; Dupérré, Nadine; Harms, Danilo (Zootaxa, 2021)
Centipedes (Myriapoda: Chilopoda) are carnivorous arthropods that live in leaf litter and soil habitats on all continents except Antarctica. Roughly 3,300 species have been described to date but the taxonomy is still progressing and requires a thorough documentation of type material and type deposits. In this paper we provide an annotated catalogue of the centipede type collection at the Zoological Museum (ZMH) in Hamburg. This collection comprises 490 type specimens belonging to 141 taxa originally described as species, subspecies and varieties. More than half of these taxa were described by the pioneering myriapodologists Carl Graf Attems (Vienna) and Karl Kraepelin (Hamburg). The collection includes material representing 93 valid species or subspecies and contains specimens predominantly from Australia (33%), Asia (22%), Africa (20%) and South America (20%). Taxonomically, the focus is on the centipede orders Scolopendromorpha (56 valid species) and Geophilomorpha (28 valid species) with fewer types for the Lithobiomorpha (8 species). A total of 48 taxa (34% of type species) have been synonymized since they were originally described and the type material for 12 additional species at the ZMH is lost. We provide a brief historical overview of this collection from its origin at the Museum Godeffroy and the Johanneum in Hamburg, including the most relevant taxonomists and collectors, followed by an annotated taxonomic catalogue with details on all species that are or were represented by type material.